The need for research on bilingualism in the history of Polish - Zarębski, Rafał (Papers in Linguistics, 2021)
Polish researchers are interested mainly in contemporary bilingualism, although recently one can observe a growing tendency to describe individual and group bilingualism from a historical perspective. Moreover, problems which were earlier considered from other perspectives are now analysed in the context of bilingual behaviours. A new approach stressing the role of bilingualism in the history of Polish is due to several factors. The most important one is the fact that a normative approach to language contacts that negatively assesses blending of languages is no longer popular. Bilingualism in the Polish linguistic past is also no longer treated as a marginal phenomenon. The aim of the article is to investigate how historical bilingualism was presented, to focus on research sources and to attempt to point out possible perspectives for further research.